INFRASTRUCTURE: A DESCRIPTIVE SURVEY OF CANDINGASINAN ELEMENTARY SCHOOL - Murni Murni; Siti Maisaroh (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
A school can be said to be effective if there is good management of facilities and infrastructure. This study aims to analyze the level of feasibility and availability of facilities and infrastructure at Candingasinan State Elementary School. This type of research is a survey with a descriptive analytical method. This research was conducted at Candingasinan State Elementary School. Data collection techniques in this study included in-depth interviews (teachers and school committee), questionnaires and documentation studies. The validity of the data collected in this study was triangulation of techniques (in-depth interviews and documentation) and sources (teachers and school committee). Data analysis techniques were collected interactively with the following stages: data reduction, data presentation, and verification. The results of the study indicate that the implementation of learning at Candingasinan State Elementary School in the use of facilities and infrastructure has been running quite well, although improvements are needed regarding facilities (student toilets and storage) and infrastructure (OHP, projectors, and whiteboards). This study is expected to provide an overview of the challenges and opportunities in improving the quality of learning facilities that support educational progress.